Determination of Nicoumalone by Isocratic RP-HPLC Method - S. SARSAMBI*, PRAKASH; GOWRISANKAR†, D. (Asian Journal of Chemistry, 2009)
A simple, rapid and reproducible high performance reversed phase liquid chromatographic method has been developed for the estimation of nicoumalone in bulk drug samples and pharmaceutical dosage forms using kromosil-C18 column. The mobile phase consists of acetonitrile and trifluroacetic acid in water in the ratio of 20:80 v/v, respectively and was pumped at rate of 1.0 mL/min at 30 °C. The detection was carried out at 254 nm and the calibration curve was linear in the range of 5 to 25 μg/mL. The method was statistically validated for its linearity, precision and accuracy. The intra-day and inter-day variation was found to be less than 1 % showing high precision of the assay method. The proposed RP-HPLC method used for determining nicoumalone in bulk drug sample or in pharmaceutical formulation.